Simulating hydrodynamics in a Rushton turbine at different stirring velocities applied to non-Newtonian fluids (2020)
In this work, gas-liquid hydrodynamics of a Rushton turbine was studied using Computational Fluid Dynamics. Different stirring conditions commonly used in fungal culture applications are simulated. Several scenarios are predicted related to gas-liquid mass transfer limitation. The above, reflected by low air dispersion reached and bubble size determinations caused by the non-Newtonian rheology, leading the process to obtain k!a values only in the order of 30 h-1 at high, stirring speeds. However, the high-power consumption in fungal culture in agitated tank bioreactors can be disadvantages in large-scale prototypes applied in nonNewtonian fluids. These Findings shown in this research should be considered as a primary criterion for optimizing mass transfer problems in large scale fungal culture applications.